DUAL EFFECTS OF FLAVONOID QUERCETIN ON RAT BASOPHILIC LEUKEMIA (RBL-2H3) CELLS : INHIBITS HISTAMINE RELEASE AND REDUCES CELL GROWTH - Zullies Ikawati; Elizabeth Wallgard; Kazutaka Maeyama (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2002)
The dual effects of the flavonoid quercetin on rat basophilic leukemia cells (RBL-2H3), tumor analog mast cells, was studied. Quercetin is known as an anti-inflammatory drug that inhibits mast cell secretion of histamine. This study aims to investigate the consequences of varying incubation times with quercetin on 2H3 cells to histamine release inhibitory action and the effects of long time incubation to the morphology of the cells. The effect of quercetin on histamine synthesis was also observed. The histamine release from the cells was inhibited by quercetin as expected, but the ability of secretion was rapidly recovered when quercetin was removed before challenging. Incubation up to 6 hours decreased the inhibitory action, but longer than 6 hours increased the inhibitory activity. In long time incubation, the cells exhibited cell damage, decreased cell growth, morphological changes, and detachment from the underlying surface in proportion with the concentration of quercetin. The instant and reversible inhibitory effects of quercetin appear to represent a first phase of actions, while reduced cell growth, elevated cell damage and morphological changes seem to be connected to a second phase. Consequently, quercetin could be considered as a compound that acts dually on RBL-2H3 cells.Key words : quercetin, histamine, RBL-2H3 cells